Complementary evaluation of potential barriers in semiconducting barium titanate by electrostatic force microscopy and capacitance–voltage measurements. (June 2022) - Prohinig, Jennifer M.; Hütner, Johanna; Reichmann, Klaus; Bigl, Stephan
Abstract: Electrostatic force microscopy (EFM) was used to directly image the impact of SiO2 content variations on the grain boundary potential barriers in semiconducting BaTiO3 -based ceramics. The grain boundary barriers were shown to be significantly thinner and more pronounced as the amount of SiO2 was increased from 0 to 5 mol%. The EFM results were confirmed by capacitance–voltage (C–V) measurements which proofs the accuracy of both methods and highlights their importance for gaining a better understanding of the interrelations between material composition and electrical properties. Graphical abstract: Image, graphical abstract